Silver inhibition, surface charge and hydrophobicity in activated sludges fed with different substrates - Kılıç, Başak. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2014., 2014)
Silver is one of heavy metals which is used in many industries. It affects the performance of biological treatment plants because of its toxic effect on microorganisms. The objective of this study is to determine the effect of silver on activated sludges fed with different substrates (a mixture consisting of glucose, peptone and sodium acetate, glucose only, peptone only). For this purpose, three semi-continuously fed batch reactors were operated for 438 days at steady-state condition. The inhibitory effect of silver was examined with the results of O2 and CO2 measurements in respirometric tests. Additionally, differences between surface charges and hydrophobicities of sludges were examined by using the colloidal titration and microbial adhesion to hydrocarbons methods, respectively. Results of the study showed that feed composition has a role on the inhibitory effect of silver ion. The sludges fed with mixed substrates and only glucose were highly affected at 4 and 5 mg/L silver addition, while the sludge fed with only peptone could tolerate these silver concentrations. This indicated that peptone reduces inhibitory effect of silver. In addition, sludges fed with mixed substrates and only glucose had higher surface charges and lower hydrophobicities compared to the sludge fed with only peptone.
Keywords: Silver -- Analysis.